Energy Economic Development in Europe - Fuinhas, José Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint explores the challenges faced by Europe as it transitions to renewable energy sources to reduce carbon emissions and enhance energy security. With 10 articles covering various countries and sectors, the book delves into issues such as solar and wind energy intermittency, the role of energy policies, and the integration of energy grids and markets. The collection also includes studies on the impact of energy policies on residential energy efficiency, the use of financial incentives for eco-friendly housing, and the benefits of district heating. The reprint aims to provide policymakers, academics, and practitioners with valuable insights into the current state of renewable energy in Europe and the policies and actions that can be taken to achieve a sustainable energy future.